Do surrounding figures' emotions affect judgment of the target figure's emotion? Comparing the eye-movement patterns of European Canadians, Asian Canadians, Asian international students, and Japanese - Masuda, Taka; Wang, Huaitang; Ishii, Keiko; Ito, Kenichi (Frontiers in Integrative Neuroscience, 2012)
Although the effect of context on cognition is observable across cultures, preliminary findings suggest that when asked to judge the emotion of a target model’s facial expression, East Asians are more likely than their North American counterparts to be influenced by the facial expressions of surrounding others (Masuda, Ellsworth, Mesquita, Leu, Tanida, & van de Veerdonk, 2008). Cultural psychologists discuss this cultural variation in affective emotional context under the rubric of holistic vs. analytic thought, independent vs. interdependent self-construals, and socially disengaged vs. socially engaged emotion (e.g., Mesquita & Markus, 2004). We demonstrate that this effect is generalizable even when (a) photos of real facial emotions are used, (b) the saliency of the target model’s emotion is attenuated, and (c) a specific amount of observation time is allocated. We further demonstrate that the socialization factor plays an important role in producing cultural variations in the affective context effect on cognition.